P123 Study of naïve and memory T helper cell response in patients of chronic rhinosinusitis with nasal polyposis (CRSwNP) after in vitro exposure to Aspergillus flavus. (20th September 2022) - Das, Shukla; Rai, Gargi; Ansari, Mohammad Ahmad; Singh, Praveen Kumar; Dar, Sajad Ahmad; Gupta, Neelima; Sharma, Sonal
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM:   Objectives: To study the CD45RA (naive) and CD45RO (memory) in CD4 + T cell population after in vitro stimulation to Aspergillus flavus antigen in CRSwNP patients and healthy controls. Methods: The study included 30 cases of CRSwNP (before and after six months of treatment) and 30 healthy controls. Postoperatively biopsies (polyp tissues) were subjected to KOH and culture for mycological investigation. Preoperatively, blood sample (4 ml) was collected from cases and controls for peripheral blood mononuclear cells (PBMCs) separation. PBMCs were treated in vitro by Aspergillus flavus antigen (20  μ g/ml) and Phytohemagglutinin and incubated for 18 h at 37°C in CO2 incubator. Cells were harvested after incubation and stained with different monoclonal antibodies such as CD3, CD4, CD45RA, and CD45RO for flow cytometry analysis. Statistical analysis was done using SPSS software. Data were expressed as mean ± SD and the significance level was considered at probability below 0.05. Results: The profiles of various CRSwNP patients and healthy controls were studied. The mean age and duration of disease of the patients were recorded as 28.92 years and 9.08 months. A total of 24/30 (80%) cases were found positive for Aspergillus flavus from KOH/culture investigation. The percentage positivity of CD3 + CD4 + T cells was significantly increased after A. flavus stimulation in patients as compared with healthy controls. Decreased levels of CD45RA + CD4 + T cells were analyzed in patients before and after treatment as compared with healthy controls. The percentage of CD45RO + CD4 + T cells was found to be increased upon A. flavus stimulation in patients compared with the healthy control group. Conclusion: The continuous exposure to fungal spores may induce unusual immune responses to Aspergillus flavus spores, triggering an allergic immunological reaction with increased CD4 + T cell responses. Increased levels of CD4 + CD45RO + T cells may transform the pathogenic reaction and highlight the chances of A. flavus reactive T cells involvement in initiating inflammation in cases of CRSwNP.